BIOACTIVITY ANALYSIS OF Annona glabra L. SEED EXTRACTS FOR WOOD PROTECTION AGAINST TERMITES (Cryptotermes cynocephalus Light. AND Coptotermes curvignathus Holmgren.) - Trisna Priadi; Nurul Chotimah; Agus Ismanto (Indonesian Journal of Forestry Research, 2021)
Pond apple (Annona glabra L.) belongs to the family of Annonaceae. The seed of A. glabra contains bioactive substance that is toxic to some organisms, however the effectiveness to control wood degrading termites has not yet been scientifically reported.  This research analyzes the efficacy of A. glabra seed extract to wood degrading termites. Seed extraction was conducted using n-hexane and ethyl acetate. The paper disc test showed that the extract of A. glabra is toxic to Cryptotermes cynocephalus (dry-wood termites) and Coptotermes curvignathus (subterranean termites). The higher extract concentration (up to 63%) resulted in a higher termite mortality (up to 100%) and lower weight loss of paper sample (less than 1%).  Ethyl acetate extract of A. glabra seeds has a better toxicity effect than n-hexane extract against dry wood termites and subterranean termites.